Awake Fiberoptic Intubation in a Patient with T4N2M1 Buccal Tumor and Pulmonary Metastasis: A Case Report and Anesthetic Challenges - Numbi Akhmadi Teguh; Jeffri Prasetyo Utomo; Taufiq Agus Siswagama (HM Publisher, 2025)
Background: Advanced buccal cancer with pulmonary metastasis presents significant challenges for airway management due to potential anatomical distortions and respiratory compromise. Awake fiberoptic intubation (AFOI) is often the preferred technique in these cases. This report describes the successful anesthetic management of a patient with a T4N2M1 buccal tumor and lung metastasis using AFOI. Case presentation: A 64-year-old male with a T4N2M1 buccal tumor and pulmonary metastasis presented for an open biopsy and biopsy of the oral cavity. He had limited mouth opening (Mallampati 2), anemia, and hypoalbuminemia. AFOI was performed using dexmedetomidine and topical lidocaine. General anesthesia was induced with propofol and atracurium and maintained with sevoflurane. Postoperative pain was managed with paracetamol and ketorolac. The patient's recovery was uneventful. Conclusion: This case highlights the importance of AFOI in securing the airway for patients with advanced buccal cancer and pulmonary metastasis. Meticulous preoperative planning, including optimization of comorbidities and vigilant perioperative monitoring, is essential for successful outcomes in these complex cases.